SER-287, AN INVESTIGATIONAL MICROBIOME THERAPEUTIC FOR PATIENTS WITH ACTIVE MILD-TO-MODERATE ULCERATIVE COLITIS, PRODUCES REMISSION ASSOCIATED METABOLITES, REDUCES INTESTINAL EPITHELIAL IL-8 SECRETION AND PROTECTS EPITHELIAL BARRIER FUNCTION IN VITRO. (21st January 2021) - Martínez, Asunción; Balasubramanian, Divya; Piña, Ambar; Kieser, Karen; Narendar, Priyanka; Abdulaziz, Ahmad; O'Brien, Edward; Henn, Matthew
Abstract: Background: In a Phase 1b study of mild-to-moderate ulcerative colitis (UC) (Henn et al. Gastro 2020), oral daily dosing of SER-287, a purified consortium of Firmicutes spores administered after vancomycin pre-conditioning, led to significantly higher rates of clinical remission compared to placebo (40% versus 0%, respectively; p=0.024). Engraftment, defined as SER-287 spore germination and growth of metabolically-active bacteria, was associated with remission and shifts in disease relevant microbe-associated metabolites. To better understand the mechanism underlying these favorable clinical observations, we evaluated metabolite production by SER-287 and their impact on specific inflammatory pathways and barrier epithelial integrity in vitro . Methods: Three SER-287 lots and a negative control pro-inflammatory consortium including three strains isolated from UC subjects ( Escherichia coli, Bifidobacterium dentium, and Streptococcus parasanguinis ) were grown in vitro in a complex medium designed to mimic the nutrient composition found in the human colon. Culture supernatants were assessed for the presence of anti-inflammatory and remission associated metabolites by GC-MS or LC-MS. Anti- and pro-inflammatory activities were determined by measuring IL-8 secretion, an inflammatory cytokine whose expression is elevated in UC patients, by HT29 epithelial cells after incubation with bacterial supernatants in the presence or absence of TNF-α. Epithelial integrity was assayed by measuring FITC-dextran leakage in a trans-well culture of differentiated primary human colonic epithelial cells challenged with IFN-γ in the presence or absence of culture supernatants. Results: When cultured in vitro, all SER-287 lots tested produced the anti-inflammatory short-chain fatty acids butyrate and propionate and other metabolites associated with remission in the Phase 1b trial, including tryptophan metabolites, bile acids and medium-chain fatty acids. SER-287 culture supernatants significantly reduced IL-8 secretion in TNF-α stimulated HT29 cells while the pro-inflammatory consortium increased IL-8 secretion compared to TNF-α alone (Figure 1A). SER-287 lots induced minimal IL-8 secretion in the absence of TNF-α while the pro-inflammatory consortium strongly induced IL-8 (Figure 1B). SER-287 supernatants significantly decreased IFN-γ-mediated barrier disruption, while the pro-inflammatory consortium was not protective (Figure 2). Conclusions: Production of remission-associated metabolites, reduction of epithelial inflammation, and protection from epithelial barrier damage are shown to be pharmacological properties of SER-287 which may underlie the mechanism of action of this microbiome therapeutic for mild-to-moderate UC.